Anhydrous conducting composite membranes composed of SPEEK/silica/ionic liquids for high-temperature proton exchange. (20th December 2016) - Li, Yuxiao; Zhang, Meishan; Wang, Xueyan; Li, Zhun; Zhao, Lianhua
Graphical abstract: Highlights: New SPEEK/silica/ionic liquids inorganic–organic composite membranes are prepared. The loss of ILs reduced when silica added into composite membranes. All composite membranes' thermal decomposition temperature is above 220 °C. The conductivity of 10 −2 S/cm was obtained for 50 wt% ILs doped composite membranes. Abstract: Sulfonated poly (ether ether ketone) (SPEEK, SP) with tetraethoxysilane (TEOS) and diethylethylammonium trifluoromethanesulfonate ([dema] [OTf]) were used to make SP/SiOx/OTf inorganic–organic composite membranes by the sol–gel method. The composite membranes were studied with respect to their structural, thermal, ionic liquid leeching (ILs), mechanical, and proton conduction properties. Fourier transform infrared spectroscopy (FT-IR) results showed that there exist intermolecular forces between the sulfonic groups, silica, and ILs in the composite membrane. Thermogravimetric (TG) results showed that the thermal stability of the SP/SiOx/OTf composite membrane is better than that of the pristine SPEEK membrane. IL leaching studies showed that the sulfonic group could help to reduce the loss of ILs. The introduction of silica in the SP/SiOx/OTf composite membrane could further reduce the loss of ILs, and also reduce the swelling degree of the composite membrane. Dynamic mechanical analysis (DMA) data showed that the introduction of silica can increase the flexibility of membranes, and improve the mechanical properties. A proton conductivity of 2.003 × 10 −2 S/cm was obtained for a 50 wt% [dema][OTf] doped SP-66/SiOx/OTF-50 composite membranes at 220 °C under anhydrous conditions.